3D WO3/BiVO4/Cobalt Phosphate Composites Inverse Opal Photoanode for Efficient Photoelectrochemical Water Splitting. Issue 16 (6th February 2017) - Zhang, Haifeng; Zhou, Weiwei; Yang, Yaping; Cheng, Chuanwei
Abstract : A novel 3D WO3 /BiVO4 /cobalt phosphate composite inverse opal is designed for photoeletrochemical (PEC) water splitting, yielding a significantly improved PEC performance.